Religious Diversity in European Prisons
XII, 192 p. 3 illus., 2 illus. in color.
Keywords: This book examines how prisons meet challenges of religious diversity, in an era of increasing multiculturalism and globalization. Social scientists studying corrections have noted the important role that religious or spiritual practice can have on rehabilitation. In the past, the historical figure of the prison chaplain operated primarily in a Christian context, following primarily a Christian model. Increasingly, prison populations (inmates as well as employees) display diversity in their ethnic, cultural, religious and geographic backgrounds. As public institutions, prisons are compelled to uphold the human rights of their inmates, including religious freedom. Prisons face challenges in approaching religious plurality and secularism, and maintaining prisoners' legal rights to religious freedom. The contributions to this work present case studies that examine how prisons throughout Europe have approached challenges of religious diversity. Featuring contributions from the UK, France, Italy, Germany, Switzerland, The Netherlands, Belgium and Spain, this interdisciplinary volume includes contributions from social and political scientists, religion scholars and philosophers examining the role of religion and religious diversity in prison rehabilitation. It will be of interest to researchers in Criminology and Criminal Justice, Social and Political Science, Human Rights, Public Policy, and Religious Studies.